2010
DOI: 10.1016/j.actaastro.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

International utilization at the threshold of “assembly complete”—science returns from the International Space Station

Abstract: The European Columbus and Japanese Kibo laboratories are now fully operational on the International Space Station (ISS), bringing decades of international planning to fruition. NASA is now completing launch and activation of major research facilities that will be housed in the Destiny U.S. Laboratory, Columbus, and Kibo. These facilities include major physical sciences capabilities for combustion, fluid physics, and materials science, as well as additional multipurpose and supporting infrastructure. Expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…And much like science in Earth‐based laboratories, predicting the timescale of the results from an investigation can be complicated and based on many different factors. The ISS program has found that after any one research activity is completed on ISS, the median time to publication is 1.5 years for completed data analysis and publication of results in a scientific journal (Ruttley et al., ).…”
mentioning
confidence: 99%
“…And much like science in Earth‐based laboratories, predicting the timescale of the results from an investigation can be complicated and based on many different factors. The ISS program has found that after any one research activity is completed on ISS, the median time to publication is 1.5 years for completed data analysis and publication of results in a scientific journal (Ruttley et al., ).…”
mentioning
confidence: 99%